Rejection sensitivity and job performance: Workplace loneliness as mediator and emotional culture of companionate love as moderator - Hafiz Ghufran Ali Khan; Muhammad Salman Chughtai; Amir Bashir; Usman Kaleem Paracha (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Incorporating the understandings from affect theory of social exchange and rejection sensitivity theory, this study investigates relationship between rejection sensitivity and job performance. This study investigates how rejection sensitivity (RS) reducesjob performance (JP) by acknowledging workplace loneliness (WL) as potential mediator and emotional culture of companionate love (ECCL) as a crucial contingency of the mediation effect. We test moderated mediation model by using sample of 291 workers and managers from textile sector at two different intervals and the analysis of data showed a negative relationship between RS and JP via WL with its decreasing strength within the ECCL. Results of our study have imperative suggestions for the organizations in vindicating the adverse effects of workers tendency towards feelings of loneliness and sensitivity towards rejection through the development of emotional culture of companionate love.
Keywords: 330; rejection sensitivity; workplace loneliness; emotional culture of companionate love; job performance; manufacturing sector